Perception of Online Anatomy Education by Medical and Dental Students at a Malaysian University: Post-COVID-19 Impact (Bangladesh Journal of Medical Education, 2025)
Introduction The COVID-19 pandemic precipitated an unprecedented shift in medical education, particularly in anatomy instruction where traditional hands-on learning was suddenly replaced by virtual methods. As educational institutions transition into the post-acute phase of the pandemic, understanding students' experiences and preferences regarding online anatomy education becomes crucial for developing effective teaching strategies. This study investigated medical and dental students' perceptions of anatomy education in the post-pandemic context, with particular emphasis on the continued utilization of online learning methodologies. Methodology: A cross-sectional study was conducted through an online questionnaire distributed to medical and dental students. The study sample comprised 128 participants, and data collection occurred between February and July 2022. The survey employed a 5-point Likert scale to evaluate various aspects of anatomy education, including the effectiveness of online teaching methods, virtual tools, and student engagement. The questionnaire assessed students' experiences with online anatomy classes, communication effectiveness, utility of virtual anatomy tools, and preferences for learning modalities. Results: The study revealed mixed perceptions regarding online anatomy education. Only 5.6% of participants strongly endorsed the enjoyability of online anatomy classes, while 29.7% expressed dissatisfaction. Communication effectiveness in online settings showed moderate acceptance, with 27.3% of students agreeing it was effective, contrasted by 19.5% who disagreed. Virtual anatomy tools received more favorable responses, with 42.4% finding cyber anatomy beneficial and 51.2% appreciating histology applications. However, concentration difficulties during online sessions were reported by 68.8% of students. A significant majority (71.2%) advocated for supplementing online classes with face-to-face practical sessions. Conclusion: The findings highlight ongoing challenges in online anatomy education despite institutional adaptations to post-acute pandemic conditions. While virtual tools demonstrate some utility in anatomy education, significant barriers to student engagement persist in online environments. The strong student preference for supplementary face-to-face sessions suggests the necessity of hybrid educational models. These results indicate that future anatomy education should integrate both digital and traditional teaching methods, leveraging the advantages of virtual tools while maintaining crucial hands-on learning experiences. This study's findings can guide educational institutions in developing more effective and student-centered anatomy education programs in the post-pandemic era.BJME, Volume-16, Issue-02, July 2025: 78-87